2015
DOI: 10.14245/kjs.2015.12.4.251
|View full text |Cite
|
Sign up to set email alerts
|

Mini-open PLIF for Moderate to High Grade Spondylolisthesis: Technique to Achieve Spontaneous Reduction

Abstract: ObjectiveThe purpose of this study was to evaluate the surgical technique and outcome of mini-open posterior lumbar interbody fusion (PLIF) under circumferential releasing technique.MethodsFourty patients who underwent mini-open PLIF using the percutaneous screw fixation system for Meyerding Grade II spondylolisthesis or more were retrospectively studied. After complete circumferential release, the slipped vertebrae would tend to obtain spontaneous reduction, and with compressive force by percutaneous screw fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“… 27 International studies have also shown similar results: excellent clinical results did not correlate with the return to work, and researchers could not evaluate work resumption because most patients remained in sickness absence for social reasons. 28 …”
Section: Discussionmentioning
confidence: 99%
“… 27 International studies have also shown similar results: excellent clinical results did not correlate with the return to work, and researchers could not evaluate work resumption because most patients remained in sickness absence for social reasons. 28 …”
Section: Discussionmentioning
confidence: 99%
“…These methods have numerous advantages, including complete decompression, instantly restored spinal stability and stable surgical efficacy. Currently, PLIF and TLIF are the standard procedures in the treatment of lumbar degenerative disc disease (21)(22)(23)(24). PTED is a technically demanding procedure with a steep learning curve, and therefore requires an experienced surgeon (25).…”
Section: Discussionmentioning
confidence: 99%